(untitled) (Revista de Artes Marciales Asiáticas, 2012)
This essay analyzes Japanese-American immigration into the American West through the prism of athletics, specifically by examining a series of contests between judoka and wrestlers from 1900 to 1920 in California. The popularity of these matches demonstrates the complex relationship between Japanese-Americans and the dominant European-American culture of the western states during this period. This complexity will be shown first by looking at the way in which martial arts are closely linked to national and ethnic identity. The strong barnstorming tradition in both judo and wrestling led to a number of matches of great interest to European-Americans of the period. These matches appealed to an interest in Japanese culture, a desire to see stereotypes reinforced, and nationalist tendencies during an age of uncertainty.